Hydrophilic syndiotactic polypropylene composite material with high crystallization temperature and preparation method thereof

By blending with polymers such as PVDF, HDPE and TPVA, the problem of poor crystallization performance of sPP is solved, and its crystallization temperature and hydrophilic properties are significantly improved, and its application areas are expanded.

CN119529421APending Publication Date: 2025-02-28SOUTH CHINA UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411709736.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The poor crystallization performance of syngastic polypropylene (sPP) makes it difficult to shape during processing, and the crystallization temperature and crystallization rate are low, which limits its application in extrusion, injection molding and other processing processes.

Method used

By blending with polymers such as polyvinylidene fluoride (PVDF) and high-density polyethylene (HDPE) at high crystallization temperature, the crystallization and hydrophilicity of PVDF, the high crystallization temperature of HDPE, and the excellent hydrophilicity of thermoplastic polyvinyl alcohol (TPVA).

Benefits of technology

The crystallization temperature and crystallization rate of sPP are significantly improved, and its hydrophilic properties are improved, thus expanding its possibilities in processing and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a hydrophilic syndiotactic polypropylene composite material with high crystallization temperature and a preparation method thereof. The composite material comprises the following components in parts by weight: 85-98 parts of syndiotactic polypropylene; 2 to 8 parts of polyvinylidene fluoride; 0-5 parts of polyethylene; and 0-8 parts of polyvinyl alcohol. The syndiotactic polypropylene composite material can be obtained by premixing the components through a high-speed mixer and then mixing and granulating through a double-screw extruder. Polyvinylidene fluoride has excellent crystallization performance and can be used as a crystallization promoting component to induce folding attachment crystallization of sPP molecular chains, the crystallization performance of sPP is improved, and meanwhile the hydrophilic performance of sPP is improved. And blending addition components such as high-density polyethylene and polyvinyl alcohol are added, and the characteristics of all the components are comprehensively utilized, so that the sPP is endowed with more excellent hydrophilic performance while the crystallization performance of the sPP is remarkably improved. The invention not only provides a brand new choice for sPP crystallization promoting components, but also expands the application field of sPP due to the brought excellent hydrophilic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials, and in particular to a hydrophilic syndiotactic polypropylene composite material with a high crystallization temperature and a preparation method thereof. Background Art

[0002] The successful development of syndiotactic-selective metallocene catalysts has made the industrial production of syndiotactic polypropylene (sPP) a reality. Compared with the most widely used isotactic polypropylene (iPP), sPP has higher toughness, better optical properties and better radiation resistance.

[0003] However, up to now, the industrialization process of sPP has been stagnant. The core reason is the poor crystallization performance of sPP, and the series of processing and molding problems it brings. The molecular configuration of sPP is that methyl groups are alternately distributed on both sides of the molecular chain. Its unique molecular structure and molecular chain movement mode make it very difficult to orderly fold and crystallize the macromolecular chain driven by temperature gradient during the finalization stage of the processing. The non-isothermal crystallization temperature of sPP with a regularity of about 80% is about 69°C, and the crystallization rate is much lower than that of iPP. This brings great difficulties to the extrusion, injection molding and other processing processes of sPP. Even if it is processed, the dimensional stability of the resulting product is also very poor, making it difficult to apply in practice. Therefore, one of the core points to improve the processing performance and use performance of sPP is to improve its crystallization performance.

[0004] A lot of exploration has shown that one of the simple and effective methods to improve the crystallization performance of sPP is to blend it with other crystalline polyolefins (with a crystallization temperature significantly higher than sPP). Studies have shown that the polyolefins that can significantly improve the crystallization performance of sPP through blending modification mainly include the following categories: other types of polypropylene (including homopolymer polypropylene iPP and random copolymer polypropylene rPP), polyethylene (mainly high-density polyethylene HDPE and linear low-density polyethylene LLDPE), crystalline copolymers containing ethylene segments (such as ethylene-vinyl alcohol copolymer EVOH, ethylene-acrylic acid copolymer EAA, etc.) and certain crystalline polyester polymers (polyhydroxyalkanoates and their copolymers PHA). Among them, HDPE has the best effect on improving the crystallization temperature of sPP, which can reach about 90°C.

[0005] The latest research and exploratory tests show that polyvinylidene fluoride (PVDF), as a thermoplastic fluorinated polymer with high crystallization temperature, high crystallization rate and high crystallinity, has a tightly arranged and stacked molecular chain with high regularity, which can also effectively promote the crystallization of sPP and improve the crystallization performance of sPP. At the same time, the molecular structure of PVDF contains fluorine atoms, which have strong electronegativity. Under appropriate conditions, fluorine atoms can act as hydrogen bond receptors to form hydrogen bonds with hydrogen atoms in water molecules, making PVDF have a certain hydrophilic tendency. When sPP and PVDF are fully melt-blended in a twin-screw extruder, the molecular chains of the two substances interweave and entangle with each other, which can improve the hydrophilicity of sPP to a certain extent. Therefore, using PVDF as a component for improving the crystallization performance of sPP not only expands the selection of blending components for improving the crystallization performance of sPP, but also gives sPP better hydrophilicity and extends the application field of sPP.

[0006] In addition, in order to further improve the hydrophilicity of SPP, thermoplastic polyvinyl alcohol (TPVA) was selected as a blending component. The molecular structure of TPVA contains a large number of hydroxyl (-OH) groups, which are polar groups that can form hydrogen bonds with water molecules, making TPVA have a strong interaction and affinity with water. At the same time, TPVA also has excellent crystallization properties.

[0007] In summary, by compounding sPP with PVDF, HDPE, TPVA and other blended additives and comprehensively utilizing the strengths of each component, the crystallization performance of sPP can be significantly improved while giving it excellent hydrophilic properties, thus obtaining a hydrophilic syndiotactic polypropylene composite material with a high crystallization temperature, expanding the application field of sPP. Summary of the invention

[0008] The object of the present invention is to overcome the above-mentioned shortcomings and deficiencies of the prior art and to provide a hydrophilic syndiotactic polypropylene composite material with a high crystallization temperature and a preparation method thereof.

[0009] The present invention is achieved through the following technical solutions: A hydrophilic syndiotactic polypropylene composite material with a high crystallization temperature comprises the following components in parts by weight: Syndiotactic polypropylene 85~98; Polyvinylidene fluoride 2~8; Polyethylene 0~5; Polyvinyl alcohol 0~8.

[0010] The melt flow rate of the syndiotactic polypropylene is 1-20 g / 10 min, the conditions are 230° C. and 2.16 kg, and the syndiotacticity is above 80%.

[0011] The melt flow rate of the polyvinylidene fluoride is 1.5-3 g / 10 min, and the conditions are 230° C. and 5 kg.

[0012] The polyethylene is high-density polyethylene with a melt flow rate of 0.5-10 g / 10 min under the conditions of 190° C. and 2.16 kg.

[0013] The melt flow rate of the polyvinyl alcohol is 1-20 g / 10 min, and the conditions are 190° C. and 2.16 kg.

[0014] A method for preparing a hydrophilic syndiotactic polypropylene composite material with a high crystallization temperature comprises the following preparation steps: Premixing: adding syndiotactic polypropylene, polyvinylidene fluoride, high-density polyethylene and polyvinyl alcohol to a high-speed mixer in sequence for premixing, the mixing temperature is 30-35° C., the speed is 200-300 rpm, and the mixing time is 3-5 minutes to obtain a premix of a syndiotactic polypropylene composite material; Twin-screw extruder mixing and granulation: the obtained premix is ​​extruded and granulated using a parallel co-rotating twin-screw extruder with a length-to-diameter ratio of 40:1 and a screw diameter of 35 mm; the feeder speed is set to 5-10 rpm, the screw speed is 150-200 rpm; the temperature of each section of the extruder is 180-220° C., to obtain the syndiotactic polypropylene composite material.

[0015] The principle of the present invention is: The unique molecular structure of sPP makes it very difficult to orderly fold and crystallize the macromolecular chains driven by temperature gradient during the finalization stage of the processing. The non-isothermal crystallization temperature of sPP with a regularity of about 80% is about 69°C, and the crystallization rate is much lower than that of iPP. At present, the most effective way to increase the crystallization temperature of sPP is to introduce other crystalline polymers as crystallization promoters to promote the attachment and crystallization of sPP molecular chains. PVDF, as a thermoplastic fluorinated polymer with high crystallization temperature, high crystallization rate and high crystallinity, has a tightly arranged and stacked molecular chain with high regularity, and can effectively act as such a crystallization promoter. After adding a certain proportion of PVDF to sPP, during the processing and cooling process, PVDF will crystallize first and become the crystallization nucleation center of the entire sPP, thereby inducing the sPP macromolecular chains to attach to the heterogeneous nucleation sites formed by PVDF to orderly fold and form a crystal structure, thereby increasing the crystallization temperature and crystallization rate of sPP. At the same time, by utilizing the hydrophilic tendency of PVDF, supplemented by adding HDPE which can greatly increase the crystallization temperature of sPP, and TPVA which contains a large number of hydroxyl groups and has excellent hydrophilic properties, a hydrophilic syndiotactic polypropylene composite material with a high crystallization temperature can be finally obtained.

[0016] Compared with the prior art, the present invention has the following advantages and effects: (1) Adding PVDF to SPP can significantly improve the crystallization properties of syndiotactic polypropylene, increase its crystallization temperature and crystallization rate, and at the same time improve the hydrophilicity of SPP to a certain extent.

[0017] (2) When adding PVDF, HDPE and TPVA can be appropriately added to obtain a syndiotactic polypropylene composite material with improved crystallization performance and effectively improve its hydrophilicity. Among them, HDPE has a more prominent effect on improving the crystallization temperature of syndiotactic polypropylene, but it is not conducive to improving its crystallization rate; when TPVA is added, the hydrophilicity of the product is greatly improved, but its crystallization temperature is reduced. When HDPE and TPVA are added at the same time, an sPP composite material with a high crystallization temperature and excellent hydrophilicity is obtained.

[0018] (3) The present invention utilizes PVDF as a component for improving the crystallization performance of SPP, and at the same time adds HDPE and TPVA, which not only provides a new choice for the component for promoting the crystallization performance of SPP, but also expands the application field of SPP due to its excellent hydrophilicity. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0020] In the embodiment of the present invention, the syndiotactic polypropylene resin is a polypropylene resin with a syndiotacticity of more than 80 mol% obtained by polymerizing propylene under the action of a metallocene catalyst, and its melt flow rate is 2-10 g / 10 min (230° C., 2.16 kg). The industrialization test product mPP6006 of the China Petroleum Research Institute can be selected, and its measured melt flow rate is 5.2 g / 10 min (230° C., 2.16 kg); the melt flow rate of polyvinylidene fluoride is 1.5-3 g / 10 min (230° C., 5 kg), and the Kynar®740 product of Arkema Co., Ltd. of France can be selected, and its melt flow rate is 2.5 g / 10 min (230° C., 5 kg). The melt flow rate of high-density polyethylene is 0.3~10g / 10min (190℃, 2.16kg). The high-density polyethylene 5000s produced by Daqing Petrochemical with a melt flow rate of about 1g / 10min can be selected; the melt flow rate of polyvinyl alcohol is 1~20g / 10min (190℃, 2.16kg). The thermoplastic TPVA-OBP special material of Sinopec Ningxia Energy Chemical can be selected. The actual measured melt flow rate is about 13g / 10min (210℃, 2.16kg).

[0021] The test results of crystallization performance in the embodiments and comparative examples of the present invention are obtained from a NETZSCH DSC214 thermal analyzer. The water contact angle test results are obtained from a German Kruss standard contact angle measuring instrument DSA25.

[0022] Example 1 Weigh the raw materials according to the following ratio: 98 parts by mass of syndiotactic polypropylene and 2 parts by mass of polyvinylidene fluoride. Premix syndiotactic polypropylene and polyvinylidene fluoride at a mixing temperature of 30°C and a speed of 200 rpm for 5 minutes. Then, add the premixed material from the feeder to the co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions are set as follows: screw speed 150 rpm, feeder speed 7 rpm, and extruder temperature of each section 180~220°C. Strand water pelletizing.

[0023] The dried syndiotactic polypropylene composite material was subjected to DSC test. All experiments were carried out in a nitrogen atmosphere. The sample mass was 5-8 mg, the heating and cooling rates were 10 K / min, and the test temperature range was 30-200 °C. The dried syndiotactic polypropylene composite material was melted at 195 °C and pressed into a 1×Φ50 mm disc for water contact angle test. The test results are shown in Table 1.

[0024] Example 2 Weigh the raw materials according to the following ratio: 95 parts by mass of syndiotactic polypropylene and 5 parts by mass of polyvinylidene fluoride. Premix syndiotactic polypropylene and polyvinylidene fluoride at a mixing temperature of 30°C and a speed of 250 rpm for 5 minutes. Then, add the premixed material from the feeder to the co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions are set as follows: screw speed 200 rpm, feeder speed 7 rpm, and extruder temperature of each section 190~220°C. Strand water pelletizing.

[0025] The dried syndiotactic polypropylene composite material was subjected to DSC test. All experiments were carried out in a nitrogen atmosphere. The sample mass was 5-8 mg, the heating and cooling rates were 10 K / min, and the test temperature range was 30-200 °C. The dried syndiotactic polypropylene composite material was melted at 195 °C and pressed into a 1×Φ50 mm disc for water contact angle test. The test results are shown in Table 1.

[0026] Example 3 Weigh the raw materials according to the following ratio: 92 parts by mass of syndiotactic polypropylene and 8 parts by mass of polyvinylidene fluoride. Premix syndiotactic polypropylene and polyvinylidene fluoride at a mixing temperature of 35°C and a speed of 250 rpm for 5 minutes. Then, add the premixed material from the feeder to the co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions are set as follows: screw speed 200 rpm, feeder speed 7 rpm, and extruder temperature of each section 185~220°C. Strand water pelletizing.

[0027] The dried syndiotactic polypropylene composite material was subjected to DSC test. All experiments were carried out in a nitrogen atmosphere. The sample mass was 5-8 mg, the heating and cooling rates were 10 K / min, and the test temperature range was 30-200 °C. The dried syndiotactic polypropylene composite material was melted at 195 °C and pressed into a 1×Φ50 mm disc for water contact angle test. The test results are shown in Table 1.

[0028] Example 4 Weigh the raw materials according to the following ratio: 90 parts by mass of syndiotactic polypropylene, 5 parts by mass of polyvinylidene fluoride, and 5 parts by mass of high-density polyethylene. Premix syndiotactic polypropylene, polyvinylidene fluoride and high-density polyethylene at a mixing temperature of 35°C and a speed of 300 rpm for 5 minutes. Then, add the premixed material from the feeder to the co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions are set as follows: screw speed 200 rpm, feeder speed 7 rpm, and extruder temperature of each section 185~220°C. Strand water pelletizing.

[0029] The dried syndiotactic polypropylene composite material was subjected to DSC test. All experiments were carried out in a nitrogen atmosphere. The sample mass was 5-8 mg, the heating and cooling rates were 10 K / min, and the test temperature range was 30-200 °C. The dried syndiotactic polypropylene composite material was melted at 195 °C and pressed into a 1×Φ50 mm disc for water contact angle test. The test results are shown in Table 1.

[0030] Example 5 Weigh the raw materials according to the following ratio: 90 parts by mass of syndiotactic polypropylene, 5 parts by mass of polyvinylidene fluoride, and 5 parts by mass of polyvinyl alcohol. Premix syndiotactic polypropylene, polyvinylidene fluoride and polyvinyl alcohol at a mixing temperature of 30°C and a speed of 300 rpm for 5 minutes. Then, add the premixed material from the feeder to the co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions are set as follows: screw speed 200 rpm, feeder speed 7 rpm, and extruder temperature of each section 185~200°C. Strand water pelletizing.

[0031] The dried syndiotactic polypropylene composite material was subjected to DSC test. All experiments were carried out in a nitrogen atmosphere. The sample mass was 5-8 mg, the heating and cooling rates were 10 K / min, and the test temperature range was 30-200 °C. The dried syndiotactic polypropylene composite material was melted at 195 °C and pressed into a 1×Φ50 mm disc for water contact angle test. The test results are shown in Table 1.

[0032] Example 6 Weigh the raw materials according to the following ratio: 87 parts by mass of syndiotactic polypropylene, 5 parts by mass of polyvinylidene fluoride, and 8 parts by mass of polyvinyl alcohol. Premix syndiotactic polypropylene, polyvinylidene fluoride and polyvinyl alcohol at a mixing temperature of 30°C and a speed of 300 rpm for 5 minutes. Then, add the premixed material from the feeder to the co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions are set as follows: screw speed 200 rpm, feeder speed 7 rpm, and extruder temperature of each section 185~200°C. Strand water pelletizing.

[0033] The dried syndiotactic polypropylene composite material was subjected to DSC test. All experiments were carried out in a nitrogen atmosphere. The sample mass was 5-8 mg, the heating and cooling rates were 10 K / min, and the test temperature range was 30-200 °C. The dried syndiotactic polypropylene composite material was melted at 195 °C and pressed into a 1×Φ50 mm disc for water contact angle test. The test results are shown in Table 1.

[0034] Example 7 Weigh the raw materials according to the following ratio: 85 parts by mass of syndiotactic polypropylene, 5 parts by mass of polyvinylidene fluoride, 5 parts by mass of high-density polyethylene, and 5 parts by mass of polyvinyl alcohol. Premix syndiotactic polypropylene, polyvinylidene fluoride, high-density polyethylene and polyvinyl alcohol at a mixing temperature of 35°C and a speed of 300 rpm for 5 minutes. Then, add the premixed material from the feeder to the co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions are set as follows: screw speed 200 rpm, feeder speed 7 rpm, and extruder temperature of each section 185~220°C. Strand water pelletizing.

[0035] The dried syndiotactic polypropylene composite material was subjected to DSC test. All experiments were carried out in a nitrogen atmosphere. The sample mass was 5-8 mg, the heating and cooling rates were 10 K / min, and the test temperature range was 30-200 °C. The dried syndiotactic polypropylene composite material was melted at 195 °C and pressed into a 1×Φ50 mm disc for water contact angle test. The test results are shown in Table 1.

[0036] Comparative Example 1 For comparison, 100 parts by mass of syndiotactic polypropylene was weighed. The syndiotactic polypropylene was added to a high-speed mixer for premixing at a mixing temperature of 30°C and a speed of 200 rpm for 5 minutes. Then, the premixed syndiotactic polypropylene was added from a feeder to a co-rotating parallel twin-screw extruder for melt extrusion granulation. The process conditions were set as follows: screw speed of 200 rpm, feeder speed of 7 rpm, and temperature of each section of the extruder of 185-220°C. The strands were water-dried and pelletized.

[0037] The dried syndiotactic polypropylene material was subjected to DSC test. All experiments were carried out in a nitrogen atmosphere. The sample mass was 5-8 mg, the heating and cooling rates were 10 K / min, and the test temperature range was 30-200 °C. The dried syndiotactic polypropylene material was melted at 195 °C and pressed into a 1×Φ50 mm disc for water contact angle test. The test results are shown in Table 1.

[0038] Table 1 Various properties of syndiotactic polypropylene and composite materials obtained in Examples and Comparative Examples As described above, the present invention can be better implemented.

[0039] The implementation methods of the present invention are not limited to the above-mentioned embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A hydrophilic syndiotactic polypropylene composite material with a high crystallization temperature, characterized in that: The composition comprises the following components in parts by weight: Syndiotactic polypropylene 85~98; Polyvinylidene fluoride 2~8; Polyethylene 0~5; Polyvinyl alcohol 0~8.

2. The hydrophilic syndiotactic polypropylene composite material with high crystallization temperature according to claim 1, characterized in that: The melt flow rate of the syndiotactic polypropylene is 1-20 g / 10 min, the conditions are 230° C. and 2.16 kg, and the syndiotacticity is above 80%.

3. The hydrophilic syndiotactic polypropylene composite material with high crystallization temperature according to claim 1, characterized in that: The melt flow rate of the polyvinylidene fluoride is 1.5-3 g / 10 min, and the conditions are 230° C. and 5 kg.

4. The hydrophilic syndiotactic polypropylene composite material with high crystallization temperature according to claim 1, characterized in that: The polyethylene is high-density polyethylene with a melt flow rate of 0.5-10 g / 10 min under the conditions of 190° C. and 2.16 kg.

5. The hydrophilic syndiotactic polypropylene composite material with high crystallization temperature according to claim 1, characterized in that: The melt flow rate of the polyvinyl alcohol is 1-20 g / 10 min, and the conditions are 190° C. and 2.16 kg.

6. The method for preparing the hydrophilic syndiotactic polypropylene composite material with high crystallization temperature according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: Premixing: adding syndiotactic polypropylene, polyvinylidene fluoride, high-density polyethylene and polyvinyl alcohol to a high-speed mixer in sequence for premixing, the mixing temperature is 30-35° C., the speed is 200-300 rpm, and the mixing time is 3-5 minutes to obtain a premix of a syndiotactic polypropylene composite material; Twin-screw extruder mixing and granulation: the obtained premix is ​​extruded and granulated using a parallel co-rotating twin-screw extruder with a length-to-diameter ratio of 40:1 and a screw diameter of 35 mm; the feeder speed is set to 5-10 rpm, the screw speed is 150-200 rpm; the temperature of each section of the extruder is 180-220° C., to obtain the syndiotactic polypropylene composite material.

Citation Information

Patent Citations

  • PP / PVDF alloy material and preparation method thereof

    CN108794890A

  • Syndiotactic polypropylene composite material with high crystallization temperature and preparation method thereof

    CN113912939A

  • High-crystallinity hydrophilic syndiotactic polypropylene composite material and preparation method thereof

    CN115895115A

  • Syndiotactic polypropylene composite material with high crystallization temperature and high crystallization rate and preparation method thereof

    CN116925468A

  • High-hydrophilicity composite plastic material and preparation method thereof

    CN118909355A